Handbook of child and adolescent drug and substance abuse pharmacological, developmental, and clinical considerations - Pagliaro, Louis A. (John Wiley and Sons, 2012)
"An insightful and comprehensive guide covering the nature of drug and substance use and abuse by children and adolescents".